Effect of organic and inorganic nutrient sources with varying row proportions on promising potato (Solanum tuberosum L.) cultivars in western plains of Uttar Pradesh - Kumar, Ajay; Verma, VS; Singh, Pushpendra; Sumeriya, HK; Sharma, Dinesh Kumar; Dadarwal, RS (Annals of Agricultural Research, 2014)
A field experiment was conducted during the rabi seasons of 2010-11 and 2011-12 to assess the effect of row proportion, organic and inorganic sources of nutrients on growth and yield of promising potato cultivars under western plains of Utter Pradesh. Three potato cultivars (Kufri Pukhraj, Kufri Anand and Chipsona-3), 3 row proportions (2:1 and 4:1 potato: mustard and sole potato/sole mustard) and 3 nutrient sources i.e 100% organic (FYM), 100% inorganic (150+80+120 kg NPK ha-1) and 50% organic + 50% through inorganic were compared. Among the elite cultivars of potato, Kufri Pukhraj recorded highest dry weight of haulm (g plant-1) at harvest, fresh and dry weight of tubers plant-1, number of tubers, total biomass and total tuber potato yield (407.15 q ha-1) Kufri Anand and Chipsona-3. Among row proportions pure potato recorded maximum plant population at initial and at harvest, 4:1 potato:mustard ratio recorded maximum haulm length at harvest, sole potato recorded maximum fresh and dry weight of tubers, total biomass, grade wise and total tuber potato yield (448.35 q ha-1). Where as in case of nutrient sources, total tuber potato yield significantly was recorded under100 % inorganic sources and this level recorded 27.66 and 2.61percent higher total potato yield over % organic and 50% organic + 50% inorganic source, respectively.